Teaching Basic Microbiology Laboratory Techniques Through e-Learning (STERILIZATX) - Mohamad Fhaizal, Mohamad Bukhori; Mohd Aminudin, Mustapha; Mohd Faizullah, Rohmon; Raziman, Imam Ghazali @ Razali; Besar, Ketol (2022)
Growing bacteria and fungus in pure culture is still one of the best and most widely used methods in learning basic microbiology. However, during the pandemic where the learning has to be conducted online, the gap in conducting the teaching has become realm. In addition, an appropriate physical environment must be created, where important factors such as hands on and observation are controlled and maintained. Therefore, the development of STERILIZATX as do it yourself (DIY) kit is timely in order to facilitate the distanced-learning requirement. The objectives of the innovation are to explain basic principle of microbial cell culture, to observe basic microbial characteristic on agar culture, and to apply basic good microbiological laboratory practice and cultivation of microbial cell culture, dedicated for distanced and e-learning. The learners are able to perform basic microbial culture aseptic technique using improvised DIY kit called STERILIZATX, observe the microbial growing pattern, distinguish and characterise the selected microbial colony, and describe the basic principles of applied microbiology in daily life during the discussion.